Inevitable decay: Debates over climate, food security, and plant heredity in nineteenth-century Britain - Lidwell-Durnin, J (Springer, 2018)
Climate change and the failure of crops are significant but overlooked events in the history of heredity. Bad weather and dangerously low harvests provided momentum and urgency for answers to questions about how best to improve and acclimatize staple varieties. In the 1790s, a series of crop failures in Britain led to the popularization of and widespread debate over Thomas Andrew Knight’s suggestion that poor weather was in fact largely unconnected to the bad harvests. Rather, Knight argued, Britain’s older varieties—particularly its fruit trees—were coming to the natural end of their lifespans. At a period when Britain was trying to maximize its agricultural land usage, Knight campaigned that his fellow farmers ought to set aside land and resources in order to cultivate new varieties—an expensive and time-consuming procedure—in order to avoid disaster. In this paper, I argue that Knight’s lifelong commitment to his position demonstrates the role played by changes in climate and weather on popular understandings of plant heredity. Further, drawing upon the historiography of Britain’s climate and agriculture, I show that despite reliable weather and good harvests, Knight’s campaign survived for several decades before the continued health of Britain’s trees was finally treated as sufficient evidence to dispense with Knight’s warnings. This case provides a means of thinking about the history of heredity as it is shaped and impacted by changes in climate and local conditions.